A review of the genus Brachysomus Schoenherr (Coleoptera: Curculionidae: Entiminae) - Yunakov, Nikolai (Zootaxa, 2022)
The genus Brachysomus Schoenherr, 1823 is reviewed. A comparative morphological study of adults from 56 Brachysomus species is provided. Redescriptions, diagnoses and identification keys are given. Descriptions of two new species are provided: B. (s. str.) podlussanyi sp. n. from Greece and B. (s. str.) pseudosetiger sp. n. from Bulgaria, which appear to be closely related to B. (s. str.) mihoki Penecke, 1914. Females of B. (s. str.) longipterus Białooki, 2007 are described. The poorly known B. (Hippomias) moczarskii Penecke, 1924 is restored from synonymy with B. (H.) oertzeni Faust, 1889. New synonyms: B. (s. str.) echinatus (Bonsdorff, 1785) = B. (s. str.) hirsutus Iablokoff-Khnzorian, 1958 syn. n. New combinations: Brachysomus (s. str.) lituratus (Reitter, 1884) comb. n. from Foucartia Jacquelin du Val, 1854; Eurosphalmus tenuicollis (Yunakov, 2006) comb. n. from Brachysomus, Eurosphalmus cribrarius (Białooki, 2007) comb. n. from Brachysomus, Nanomias skodai (Białooki, 2007) comb. n. from Brachysomus, and Chiloneus bonnairei (Hoffmann, 1942) comb. n. from Brachysomus. Lectotypes are designated for: Strophosomus hirtus Boheman, 1845; Brachysomus ornatus Stierlin, 1892; B. bensae Stierlin, 1893; Platytarsus fasciatus Stierlin, 1899; and P. setiger Gyllenhal, 1840. For each species, all known localities are presented on a distribution map. Ecological preferences of Brachysomus species are specified. First records of Brachysomus (s. str.) fremuthi Košťál, 1991 from Romania, B. (Hippomias) carpathicus Košťál, 1992 from Serbia, and B. (H.) ponticus Apfelbeck, 1898 from Greece are given.